SENSIBILIDADE DE MUDAS DE MAMOEIRO A PRODUTOS ALTERNATIVOS NO CONTROLE DE PRAGAS - Cardoso, Suane Coutinho; GonÃ§alves, Joaquim Alves; Nunes, Maiara de Souza; Carvalho, Carlos Alfredo Lopes de; Peixoto, Clovis Pereira (REVISTA DE AGRICULTURA, 2015)
SENSIBILIDADE DE MUDAS DE MAMOEIRO A PRODUTOS ALTERNATIVOS NO CONTROLE DE PRAGAS